A Comparative Analysis of the Ocular Microbiome: Insights into Healthy Eyes and Anophthalmic Sockets - Francisco Zamorano-Martín; Guillermo Chumaceiro; Pablo Navarro-Torres; Davide Borroni; Facundo Urbinati; Ángel Molina; Andreu Paytuví-Gallart; Carlos Rocha-de-Lossada (Microorganisms, 2024)
The purpose of this study is to characterize the ocular surface microbiota of patients with an anophthalmic cavity. An eNAT with 1 mL of Liquid Amies Medium was used to collect samples. Microbial DNA from anophthalmic socket and healthy fellow control eye samples was isolated and sequenced. Raw reads were analyzed with GAIA (v 2.02). The richness and Shannon alpha diversity metrics, as well as Bray–Curtis beta diversity and Wilcoxon signed-rank test values, were computed with R packages such as phyloseq, mia, or DESeq2 to allow for microbiome analysis. Principal coordinate analysis (PCoA) was performed using the function plotReducedDim from the R package scater. The different taxonomic profiles were described under the concept of eye community state type (ECST). The microbiomes of both eyes from 25 patients with an anophthalmic cavity were analyzed in this study. While the microbial communities of paired eyes from the same patients showed notable dissimilarity, no consistent patterns emerged when comparing healthy eyes to anophthalmic sockets. Alpha diversity values did not significantly differ between healthy eyes and anophthalmic socket samples, though there was considerable variability within each group. Notably, anophthalmic socket samples generally exhibited lower abundances of genera such as Staphylococcus, Enterococcus, Paenibacillus, and Sediminibacterium compared to their healthy counterparts. Microbial variability between healthy eyes and anophthalmic sockets may be due to anatomical differences. Further research is needed to determine whether patients without anophthalmic sockets exhibit similar microbiome patterns in both eyes.